2020
DOI: 10.7717/peerj.9676
|View full text |Cite
|
Sign up to set email alerts
|

Medial knee cartilage is unlikely to withstand a lifetime of running without positive adaptation: a theoretical biomechanical model of failure phenomena

Abstract: Runners on average do not have a high risk of developing knee osteoarthritis, even though running places very high loads on the knee joint. Here we used gait analysis, musculoskeletal modeling, and a discrete-element model of knee contact mechanics to estimate strains of the medial knee cartilage in walking and running in 22 young adults (age 23 ± 3 years). A phenomenological model of cartilage damage, repair, and adaptation in response to these strains then estimated the failure probability of the medial knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 83 publications
4
26
2
Order By: Relevance
“…For this reason, such models were not useful for assessing the influence of degenerative changes on the pathomechanism of degenerative meniscal injury. The process of cartilage degeneration and damage was simulated in recent works ( Liukkonen et al, 2017 ; Miller & Krupenevich, 2020 ). Peters et al (2018) suggested that computational models of the knee joint should be constructed using material parameters and geometry from cohorts with consistent disease state.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, such models were not useful for assessing the influence of degenerative changes on the pathomechanism of degenerative meniscal injury. The process of cartilage degeneration and damage was simulated in recent works ( Liukkonen et al, 2017 ; Miller & Krupenevich, 2020 ). Peters et al (2018) suggested that computational models of the knee joint should be constructed using material parameters and geometry from cohorts with consistent disease state.…”
Section: Introductionmentioning
confidence: 99%
“…The peak net (N) and normalized medial tibiofemoral forces (BW) were calculated using data derived from the joint reaction analysis. The cumulative medial tibiofemoral load was computed as the quotient of the mean stance phase medial tibiofemoral force and the stride length [ 35 ]. Pilot walking data shows a minimal detectable difference (MDC) of 0.27 BW and a high level of reliability (ICC = 0.951) for the peak medial tibiofemoral force ( Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The medial tibiofemoral contact forces obtained from OpenSim were input into a model of medial knee contact mechanics which was utilized to calculate tibiofemoral cartilage stress and strain via adapted MATLAB source code [ 35 ]. Pilot walking data shown MDCs of 0.01 and 0.16 MPa and high reliability (ICC ≥ 0.945) for indices of medial tibiofemoral stress and strain ( Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations